Towards the Unification of Inconsistency Handling Mechanisms - Batens, Diderik (Logic and Logical Philosophy, 2000)
It is shown that the (flat) consequence relations defined from the Rescher-Manor Mechanism (that is: in terms of maximal consistent subsets of the premises) are all inconsistency-adaptive logics combined with a specific interpretation schema for the premises. Each of the adaptive logics is obtained by applying a suitable adaptive strategy to the paraconsistent logic CLuN. This result provides all those consequence relations with a (dynamic) proof theory and with a static (as well as a dynamic) semantics.